Relationship between Scientific Argumentation Skills and Students' Scientific Literacy Skills - Rina Delfita; Fatma Setiawati; Diyyan Marneli; Aidhya Irhash Putra (Magister Pendidikan Biologi, Universitas Negeri Medan, 2022)
Learning models that develop students' argumentation and critical thinking skills are widely applied in senior high school. The purpose of this study was to verify the correlation between argumentation skills and scientific literacy skills of high school students on cell matter as the smallest structural and functional unit of life and cell bioprocesses. This research uses a correlational method. The sample of this research was the students of class XI MIPA SMAN 1 Batusangkar, numbering 34 people. Data on argumentation skill and scientific literacy skill were obtained from the test results in the form of an essay test using socio-scientific issues. Descriptive statistics, Pearson product moment correlation analysis techniques, and path analysis were used for data analysis. The results showed that there was a significant and positive relationship between argumentation skills and scientific literacy skills. In addition, argumentation skills have a statistically positive predictive effect on scientific literacy skills. It was revealed that argumentation skills acted as a partial mediating variable, so as stated in the theory, argumentation skills and scientific literacy skills were found to be very closely related. Thus, students' argumentation skills can be used to predict students' scientific literacy skills.